DIGITAL FINANCE ADOPTION STRATEGY IN SHARIA BPR - Hasibuan, Putri Septi Naulina; Rinawati, Liya; Harno, Rinto (Transpublika Publisher, 2023)
The emergence of Financial Technology has not only transformed conventional banking businesses but also Islamic banking. This is evident from the increasing collaborations between Islamic banks and Fintech companies. The purpose of this research is to examine the relationship between perceived risk, perceived benefits, financial literacy, and the intention to adopt digital finance in the Islamic banking sector. The study was conducted using a correlational research design and data were collected from 85 customers of Islamic banks through questionnaires. The data were analyzed using multiple linear regression analysis. The findings indicate that perceived risk has no significant influence on the intention to adopt digital finance in Islamic banking. On the other hand, perceived benefits and financial literacy have a significant positive influence on the intention to adopt digital finance in the Islamic banking sector.